Case report: Successful remission with upadacitinib in a young patient with anti-TNF-refractory intestinal Behçet’s disease - Sha, Sumei; Xu, Bin; Wang, Kairuo; Qiao, Chenyang; Shi, Haitao; Jiang, Jiong; Quan, Xiaojing; Liu, Xin (Frontiers in Immunology, 2024)
BackgroundThe limited therapeutic options and inconsistent treatment efficacy of Intestinal Behçet’s disease complicate its management, with the absence of standardized guidelines further exacerbating the challenges faced by clinicians.Case PresentationIn this case report, we present a patient with refractory intestinal Behçet’s disease who experienced treatment failure with prior biologic agents. This case sheds light on managing this complex scenario with Janus kinase (JAK) inhibitors, the patient achieved mucosal healing after switching to Upadacitinib.ConclusionThis case underscores the potential of Upadacitinib as an effective alternative for managing difficult cases of intestinal Behçet’s disease.